TINGKAT PENGETAHUAN ORANG TUA TENTANG STIMULASI DAN PERKEMBANGAN MOTORIK HALUS ANAK PRASEKOLAH USIA 3-5 TAHUN - Wahyu Jatmiko; Rosa Delima Ekwantini; Miftafu Darussalam (MEDIA ILMU KESEHATAN, 2015)
Background: Knowledge means everything which is known or intelligence relates to something. Knowledge or cognition is an important basis to establish one's actions. Stimulation is defined as a basic ability to encourage activity of children aged 0-6 years to achieve optimum growth and development. Objective: (1) To identify the level of parents’ knowledge regarding early child stimulation; (2) to identify the development of fine motor skills of preschool children; (3) to identify correlation between parents’ knowledge and their children’s fine motor skills. Methods: A cross-sectional studi using total sampling consisted of 37 respondents from Hargotirto village in Kulonprogo district, Yogyakarta. Data were taken by using a questionnaire to identify the knowledge and the Denver Developmental Screening Test to assess the development respectively and then were analyzed by using Gamma Statistical Test. Results: The results showed that: (1) The level of parents knowledge regarding early child stimulation, mostly good (37.7%); (2) The development of fine motor skills of the children were mostly at normal range (73%); (3) There was moderate level of correlation between parents’ knowledge and their children’s fine motor skills (R=.528, p<.05) Conclusion: There is a correlation between parents’ knowledge and preschool children’s fine motor skills. Keyword: Knowledge level, stimulation, fine motor skills